Gap Analysis of the Perceived and Expected Quality of Services Provided by Urban Family Physicians - Ebrahim Jafaripooyan; Abbas RahimiForoushani; Fatemeh Gharbi (Kerman University of Medical Sciences, 2019)
Gap Analysis of the Perceived and Expected Quality of Services Provided by Urban Family Physicians   Jaafaripooyan Ebrahim1, Rahimi Forooshani Abbas2, Gharbi Fatemeh3*   1. Associate Professor, Department of Health Management and Economics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran 2. Professor, Department of Epidemiology and Biostatistics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran 3. MPH Health Insurance, MSc in Mathematical Statistics, Iran Health Insurance Organization, Shiraz, Iran * Corresponding Author: Fatemeh Gharbi Address: General Health Insurance Office, North Vesal St., Shiraz, Iran Tel: 00987132111142                                                Email: Gharbi.f@gmail.com Abstract: Background & Objectives: The principal purpose behind the initiation of the urban family physician plan in the health care system is to provide equity, create a referral system and increase the responsiveness towards patients in line with their demands and expectations. The present study aimed to evaluate the expected and perceived quality of services provided by urban family physicians in the city of Shiraz from the viewpoints of patients. Methods: This cross-sectional descriptive-analytical study was conducted in 2019. A number of 300 patients referred to urban family physician private clinics in Shiraz city were selected using classified two-step clustering method. Data were collected using a researcher-developed questionnaire. Mann-Whitney, Wilcoxon and Kruskal-Wallis tests were used for data analysis through SPSS24 software package. Results: In all dimensions except for "continuity" and "access", there was a significant difference between perceived and expected quality of service. The largest gap was related to "timing" and the least gaps were related to "continuity", "access" and" perceived effectiveness".  Conclusion: The gap between patients' perceived and expected quality of services requires managers' more attention to the quality improvement programs to provide more patient satisfaction. This gap can be modified by proper management, monitoring, and training patients and health care providers.   Keywords: Service quality, Urban family physician, Private clinic, Patients, Expectations and Perceptions   Citation: Jaafaripooyan E, Rahimi Forooshani A, Gharbi F. Gap Analysis of the Perceived and Expected Quality of Services Provided by Urban Family Physicians. Journal of Health Based Research 2019; 5(3): 319-31. [In Persian]